2021
DOI: 10.1097/ftd.0000000000000850
|View full text |Cite
|
Sign up to set email alerts
|

High Intrapatient Variability in Tacrolimus Exposure Calculated Over a Long Period Is Associated With De Novo Donor-Specific Antibody Development and/or Late Rejection in Thai Kidney Transplant Patients Receiving Concomitant CYP3A4/5 Inhibitors

Abstract: Background: High intrapatient variability in tacrolimus trough levels (Tac IPV) is associated with poor allograft outcomes. Tac IPV was previously calculated using trough levels 6-12 months after kidney transplantation (KT). Data on the accuracy of Tac IPV calculation over a longer period, the association between high Tac IPV and donor-specific antibody (DSA) development after KT in Asian patients, and the role of IPV in patients receiving concomitant cytochrome P450 (CYP)3A4/5 inhibitors (CYPinh) are limited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(500 reference statements)
0
5
0
Order By: Relevance
“…A reduction in steroid dosage, decreased CYP3A4 activity, and increased hematocrit and albumin with time are plausible explanations for the decline of tacrolimus apparent clearance after KT [ 5 , 39 ]. Timing after KT during which tacrolimus exposure is used for IPV calculation is, therefore, one possible explanation for the differences in IPV values reported among previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A reduction in steroid dosage, decreased CYP3A4 activity, and increased hematocrit and albumin with time are plausible explanations for the decline of tacrolimus apparent clearance after KT [ 5 , 39 ]. Timing after KT during which tacrolimus exposure is used for IPV calculation is, therefore, one possible explanation for the differences in IPV values reported among previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 95%
“…Different methods have been used to quantify IPV of tacrolimus among studies that reported the associations between high tacrolimus IPV and poor long-term outcomes. The coefficient of variation and mean absolute deviation are commonly utilized to calculate tacrolimus IPV [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 ]. A minimum of three C0 concentrations have been included in the calculation of tacrolimus IPV for each patient among studies [ 8 , 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sofosbuvir based therapies could also have an interaction with Tacrolimus. Intra‐patient variation in tacrolimus trough levels have been associated with increased risk for rejection and development of de novo DSA 40–42 . Theoretically, it is possible that recipients of HCV NAT+ organs were more prone to intra‐patient variability in tacrolimus trough level due to such drug interaction which might have contributed to the higher incidence of de novo DSA.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that high Tac IPV [7,[14][15][16] or low C 0 /D [3,6,17] may cause eGFR decline, graft rejection, or loss in the late post-transplant period. Still, it has not been entirely elucidated whether or not these parameters should be considered simultaneously.…”
Section: Discussionmentioning
confidence: 99%